2010
DOI: 10.1021/om100850p
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Hindered Diazabutadienes (DABs): Competing Reaction Pathways with MeLi

Abstract: Treatment of N,N 0 -bis(2,6-diisopropylphenyl)-1,4-diaza-2,3-dimethyl-1,3-butadiene with MeLi results in carbon-carbon bond formation and selective reduction of one of the imine arms to give the N-lithiated salt of the imine/amine, N,N 0 -bis(2,6-diisopropylphenyl)-1,4-diaza-2,3,3-trimethyl-1-butene. This compound crystallizes from Et 2 O as a solvent adduct, exists as a monomer both in solution and the solid state, and features a three-coordinate lithium nucleus that is chelated to oxygen, amido, and imino do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
(21 reference statements)
2
27
0
Order By: Relevance
“…For Me2 DAD Dipp , deprotonation of the central methyl groups has been observed in some cases. [38,39] Moreover, a number of structurally closely related alkali metal complexes are known, in which the two central carbon atoms of the ligand are part of an additional aromatic system (for instance, derivatives of ortho-phenylenediamine). [40][41][42][43] However, all these com-plexes have been obtained under different conditions and comprise a variety of solvent co-ligands, which makes comparison difficult.…”
Section: Introductionmentioning
confidence: 99%
“…For Me2 DAD Dipp , deprotonation of the central methyl groups has been observed in some cases. [38,39] Moreover, a number of structurally closely related alkali metal complexes are known, in which the two central carbon atoms of the ligand are part of an additional aromatic system (for instance, derivatives of ortho-phenylenediamine). [40][41][42][43] However, all these com-plexes have been obtained under different conditions and comprise a variety of solvent co-ligands, which makes comparison difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of diimines with metal alkyls is a convenient route to iminoamine ligands [28,29]. For diimines with unsubstituted backbones, the initial R-M addition across one imine double bond is followed by a hydrogen migration, so that the imine carbon bears the new substituent.…”
Section: Resultsmentioning
confidence: 99%
“…A two‐step phase cycle was used to remove the unwanted echoes. Relaxation‐filtered hyperfine (REFINE) spectroscopy was also applied to obtain at least a qualitative picture of the paramagnetic species present in the sample. For REFINE measurements, a pulse sequence of (π-Tf-π/2-τ-π/2-T-π/2 ) together with a four‐step phase cycle were used.…”
Section: Methodsmentioning
confidence: 99%
“…The so‐far‐reported EPR spectroscopy results on DAD complexes have mostly indicated that the unpaired electron is delocalized over the DAD backbone, and therefore, a dominant ligand‐centered character with small g and A anisotropies is generated. However, there are other cases that report weak or rather strong delocalization into metal centers in addition to the DAD backbone …”
Section: Introductionmentioning
confidence: 99%